THE NEUROPROTECTIVE POTENTIAL OF COFFEE COMPOUNDS IN THE PREVENTION AND PROGRESSION OF NEURODEGENERATIVE DISORDERS: A SYSTEMATIC REVIEW FOCUSING ON ALZHEIMER’S AND PARKINSON’S DISEASES - Jóźwicka, Agnieszka; Janikowski , Wojciech; Bąkowska , Ewa; Stępka, Aleksandra; Jaworowicz, Lena; Plichtowicz-Kordowska, Weronika; Lewandowska, Karina; Awad, Sara; Szymonek, Paweł; Zysk, Adam (International Journal of Innovative Technologies in Social Science, 2026)
Background: Neurodegenerative disorders (NDDs), particularly Alzheimer’s disease (AD) and Parkinson’s disease (PD), present a profound and growing global health burden with a notable lack of disease-modifying therapies. Emerging epidemiological and preclinical evidence suggests that habitual coffee consumption may confer significant neuroprotective benefits, driven by its complex matrix of bioactive phytochemicals. Objective: This systematic review aims to critically evaluate the efficacy and underlying molecular mechanisms of coffee-derived compounds in the prevention and progression of Alzheimer’s and Parkinson’s diseases. Methods: A comprehensive literature search was conducted across PubMed and Google Scholar databases using predefined Medical Subject Headings (MeSH) and keywords. The review synthesized data from epidemiological cohorts, clinical trials, and preclinical models focusing on caffeine and non-caffeine constituents, such as chlorogenic acids and phenylindanes. Results: Coffee exerts neuroprotective effects through a synergistic, multi-target approach. Caffeine primarily acts via adenosine A2A receptor antagonism, enhancing dopaminergic signaling and reducing excitotoxicity, which strongly correlates with a reduced risk of PD (relative risk ranging from 0.65 to 0.80). Non-caffeine constituents provide robust antioxidant and anti-inflammatory activity, upregulating the Nrf2 pathway and directly inhibiting the aggregation of amyloid-beta, tau, and alpha-synuclein proteins. While epidemiological evidence for PD is highly consistent, data regarding AD is more variable; however, regular midlife coffee consumption is significantly associated with a reduced risk of late-life cognitive decline. Individual responses are notably modulated by genetic polymorphisms (e.g., CYP1A2). Conclusion: Coffee represents a potent, biologically plausible dietary intervention with significant potential to mitigate NDD pathology. While its multifaceted mechanisms position it as a promising neuroprotective agent, particularly against PD, further rigorous randomized controlled trials are essential to establish causality and define optimal, personalized consumption guidelines.